Molecular Identification of Bacterial Infections in Children with Intermittent Peritoneal Dialysis - Rafeef Yousif Rasheed (Journal of Global Pharma Technology, 2018)
Background: Bacteria is a major cause of peritonitis infections and it is very important to have a reliable test to detect these bacteria in peritoneal fluid by molecular methods. Aims of the study: Detection of the most common bacteria in peritoneal fluid from pediatric patients with acute and chronic renal failure who undergo peritoneal dialysis, through molecular diagnostic methods. Methods: One hundred clinical peritoneal fluid isolates were submitted to molecular methods (Polymerase chain reaction (PCR) and DNA sequencing) for detection. Results: By molecular methods according to PCR technique, the following bacteria were identified: S. aureus which was seen in 17 (17.0%) of samples, S. epidermids which was identified10 (10.0%) and Pseudomonas spp. which was identified 10 (10.0%) and according to DNA sequencing technique, the following bacteria were identified: S. aureus10(10.0%) of samples, S. epidermids 16 (16.0%), E.coli 6 (6.0%),Bacillus spp. 8 (8.0%). Streptoccous and Microccous1 (1.0 %) for each one. Conclusion: The most common bacterial were the best. pathogene responsible for peritonitis were S. aureus, Psudomonasspp., S. epidermids, and E. coli.Keywords: Peritonitis, Molecular detection of bacterial peritonitis, Peritoneal dialysis infections.